نقد المتن عند الامام مسلم من خلال كتابه التمييز -دراسة نظرية تطبقية- - حاصي, خولة (University Of Eloud جامعة الوادي, 2019)
"يقوم هذا البحث بدراسة نقد المتن عند الإمام مسلم من خلال كتابه ""التمييز""، وقد انبنى من مقدمة وثلاثة مباحث وخاتمة، حيث خصصت المقدمة للتعريف بالموضوع و أهميته وأسباب اختياره، ثم قمت في المبحث الأول بوضع مدخل حول مفهوم نقد المتن عند المحدثين، أما المبحث الثاني، فكان للتعريف بالإمام مسلم وكتابه ""التمييز""، أما المبحث الثالث والأخير فكان دراسة تطبيقية لقرائن تعليل المتن عند الإمام مسلم، وقد خلص البحث بجملة من النتائج أهمها: أن نقد المتن عند المحدثين يتمثل في تمحيص وتمييز متون الأحاديث مع بيان أسباب وقرائن تعليها بمعايير وضوابط معلومة، والحكم على تلك المتون إما قبولا، أو رداً، أن للإمام مسلم كلاما صريح حول نقد المتن داخل كتابه ""التمييز"" والتي تعرف بمقاييس أو معايير نقد المتن، وكذلك خلصت في هذا البحث أن من المعايير نقد المتن المتوافق عليها عند الإمام مسلم-رحمه الله- وغيره من نقاد المحدثين تتمثل في مخالفة الحديث للقرآن الكريم، مخالفة الحديث للأخبار الصحيحة الثابتة والمشهورة، ومخالفته للأحداث التاريخية، ومخالفته للعقل، أو بسبب الشذوذ... وغيرها الكثير. " "This study is dealing with the content criticism of Al Hadith accordimg to imam Muslim through his book ""Al Tamyeez"" which means discrimination and it contains an introduction three chapeters and a conclusion. The introduction defines the subjects its importance and reasons of hoosing it. The first chapeter contains criticism of Hadith according to scholars or narrators(MuhadiHin).the seond chapeter introduces AL Imam Muslim and his book ""Al Tamyeez"". The third one and the last it is about the practical study to clues and explanation of the text ""Metn"" according to Imam Muslim As a result content criticism according to scholars is to dixriminate and audit HL Hadith with reasons and evidences standards and known regulations and judging it whether by accepting or rejecting. Al Imam Muslim has clear oppnvion about content criticism of AL Hadith in his book ""Al Tamyeez"" known as Metrics or standards of criticisn of text Meten Through this study I realized that these standards and agreement between Imam Muslim and other scholars is about the dejerence between The Quran and AL Hadith the deference between Al Hadith and the correct and fsied known text also the defferente between AL Hadith and the historical events and the logic and others. "
مذكرة ماستر تخصص علوم الحديث
Keywords: النقد - المتن - مسلم- التمييز; Criticism - Metn - Muslim - Discrimination